Рівні сформованості готовності студенів факультетів мистецтв до впровадження інновацій у процес фахового навчання - Лю Чуньцзян; Lіu Chunjiang (Видавництво «Код», 2025)
Резюме. Cтаття розкриває специфіку готовності студентів факультетів мистецтв до впровадження інновацій у процес фахового навчання, що забезпечує сформованість компетентності майбутніх учителів музичного мистецтва у полі новаторського вирішення завдань на межі знань різних дисциплін. Для оцінювання рівнів сформованості готовності студентів факультетів мистецтв до впровадження інновацій у фахову діяльність нами обрано триступеневу систему рівнів, а саме: пізнавально-репродуктивний (низький), діяльнісно-творчий (досконалий), художньо-емоційний (високий).

Abstract. The article reveals the specifics of the readiness of students of art faculties to implement innovations in the process of professional training, which ensures the formation of the competence of future teachers of musical art in the field of innovative problem solving at the border of knowledge of various disciplines. To assess the levels of readiness of students of art faculties to implement innovations in professional activity, we have chosen a three-level system of levels, namely: cognitive-reproductive (low), activity-creative (perfect), artistic-emotional (high). The cognitive-reproductive level is characterized by the inability of students of art faculties to transfer acquired theoretical knowledge to the practical plane, they almost completely lack an algorithm for performing creative tasks. Students, whom we have attributed to the cognitivereproductive level, do not have the desire to make their own interpretations of musical works, their psychological and pedagogical skills are superficial. Students, whom we have attributed to the activity-creative level of readiness for the implementation of innovations, are interested in innovative teaching methods, work on creating creative projects. They have systemic professional competencies, try to independently use multimedia tools. The artistic-emotional level is manifested in students of the faculties of arts by a new type of thinking, the characteristic features of which are the creation of a single plane of artistic knowledge from disparate disciplinary spheres. They demonstrate the ability to reflect, self-analysis, which implies a high degree of readiness of future teachers of musical art for innovative professional training.
Levels of formation of readiness of students of faculties of arts to implement innovations in the process of professional training
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: студенти факультетів мистецтв; готовність до впровадження інновацій; рівні сформованості; компетентність; творчість; фахове навчання